2018
DOI: 10.1136/bmjopen-2018-023544
|View full text |Cite
|
Sign up to set email alerts
|

Mental health-related emergency department presentations and hospital admissions in a cohort of urban Aboriginal children and adolescents in New South Wales, Australia: findings from SEARCH

Abstract: ObjectivesThe aim of the current study is to quantify mental health-related emergency department (ED) presentations and hospitalisations, and associated child and family characteristics, in children recruited through four Aboriginal Community Controlled Health Organisations.SettingFour Aboriginal Community Controlled Health Services that deliver primary care. All services were located in urban or large regional centres in New South Wales, Australia.Participants1476 Aboriginal children aged 0–17 years at recrui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 42 publications
0
20
0
Order By: Relevance
“…The centrepiece of the programme is the SEARCH cohort study, which is the largest cohort study of urban Aboriginal children in Australia 45. The current qualitative study on mental healthcare pathways was initiated in response to findings from the SEARCH cohort study which showed high rates of Aboriginal young people at risk for emotional and behaviour problems,4 data linkage work which illustrated high rates of mental health-related hospitalisation for Aboriginal young people for mental health problems30 and qualitative data highlighting community concerns around mental health 27. As most research published thus far has examined general Aboriginal child and adolescent mental health, for this paper, mental health problems will be defined broadly as behavioural or emotional problems or associated impairment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The centrepiece of the programme is the SEARCH cohort study, which is the largest cohort study of urban Aboriginal children in Australia 45. The current qualitative study on mental healthcare pathways was initiated in response to findings from the SEARCH cohort study which showed high rates of Aboriginal young people at risk for emotional and behaviour problems,4 data linkage work which illustrated high rates of mental health-related hospitalisation for Aboriginal young people for mental health problems30 and qualitative data highlighting community concerns around mental health 27. As most research published thus far has examined general Aboriginal child and adolescent mental health, for this paper, mental health problems will be defined broadly as behavioural or emotional problems or associated impairment.…”
Section: Methodsmentioning
confidence: 99%
“…The last 5 years has seen an increase in funding for mental health services and programmes for Aboriginal people 29. However, recent data show Aboriginal young people being hospitalised for mental health events at a significantly higher rate than the general population,30 and rates of suicide among young Aboriginal people remain high 31. While there are systematic reviews of Indigenous mental health programmes available internationally,32 in the Australian context, the small amount of published work that exists has largely been descriptive 33.…”
Section: Introductionmentioning
confidence: 99%
“…[40][41][42] In 2 studies, participants were recruited from health services that specifically provided care to Indigenous groups. 43,44 In the remaining 2 studies, parental Indigeneity was determined through offspring self-identification. 33,45 Tables 1, 2, and 3 contain descriptions of included studies, categorized by parental mental health challenge (i.e., poor parental mental health [broadly defined], parental substance misuse, and maternal internalizing issues and arranged in ascending order of offspring age [youngest to oldest] with studies containing non-Indigenous comparison groups being listed first).…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…Seven studies were conducted in the United States, 32,[34][35][36][37][38]42 and 2 each in Taiwan, 33,45 New Zealand, 40,41 and Australia. 43,44 One included Indigenous groups from Canada and the United States. 39 Five studies included measurements of both maternal and paternal mental health, 32,33,[36][37][38] 6 of maternal mental health only, 34,35,[39][40][41][42] and 3 studies did not specify whether parental mental health was that of mothers, fathers, or both.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation